Demystifying the role of MMP9 and TIMP-1 as markers of lung imaging and functional abnormality of COVID-19 - Alfian N Rosyid; Arina D Puspitasari; Anggraini D Sensusiati; Jusak Nugraha; Muhammad Amin (Journal of Infection in Developing Countries)
Introduction: This study aimed to analyze the levels of MMP-9 and TIMP-1 as biomarkers for identifying lung anatomical and functional abnormalities in coronavirus disease 2019 (COVID-19).